2017
DOI: 10.1155/2017/2162078
|View full text |Cite
|
Sign up to set email alerts
|

Hand Motion and Posture Recognition in a Network of Calibrated Cameras

Abstract: This paper presents a vision-based approach for hand gesture recognition which combines both trajectory and hand posture recognition. The hand area is segmented by fixed-range CbCr from cluttered and moving backgrounds and tracked by Kalman Filter. With the tracking results of two calibrated cameras, the 3D hand motion trajectory can be reconstructed. It is then modeled by dynamic movement primitives and a support vector machine is trained for trajectory recognition. Scale-invariant feature transform is employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…For example, Tsai [ 20 ] and Zhang [ 21 ] proposed a planar patterned object in order to calibrate a single camera in a small field of view (FoV). Other calibration objects such as spheres were used for better analysis of camera calibration such as conic extraction that was proposed by Lu and Payandeh [ 22 , 23 ] and Wang and Payandeh [ 24 ].…”
Section: Background Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Tsai [ 20 ] and Zhang [ 21 ] proposed a planar patterned object in order to calibrate a single camera in a small field of view (FoV). Other calibration objects such as spheres were used for better analysis of camera calibration such as conic extraction that was proposed by Lu and Payandeh [ 22 , 23 ] and Wang and Payandeh [ 24 ].…”
Section: Background Materialsmentioning
confidence: 99%
“…For instance, Krumm et al [ 25 ] and Dai and Payandeh [ 26 ] demonstrated on how a single or multiple object can be labeled and tracked across multiple RGB surveillance cameras. Using two cameras, Wang and Payandeh [ 24 ] studied hand motion and posture recognition, and Gao et al [ 27 ] investigated a full body motion capture. In order to integrate data from multiple sensors, it is required that both their intrinsic parameters and their relative locations (i.e., extrinsic parameters) be determined in order to increase accuracy and correspondences between cameras [ 23 ].…”
Section: Background Materialsmentioning
confidence: 99%
“…e availability of low-cost small-sized cameras attached to wearable sensors and portable imaging devices has opened up a wide range of imaging-oriented applications, including assisted living, smart healthcare, traffic monitoring, virtual sports experiences, and posture recognition [1][2][3][4][5][6][7][8][9][10][11][12]. An interconnection of visual sensor nodes (sensor nodes with attached camera) is known as visual sensor network (VSN) [13,14] or as wireless multimedia sensor network (WMSN) [15,16].…”
Section: Motivationmentioning
confidence: 99%
“…Hand gesture recognition is significant for humancomputer interaction (HCI) and can simplify many essential applications in electronic devices, digital games, automobiles, and defense [1]. Hand gesture recognition has the potential to overcome dependency on the use of conventional HCI devices such as the mouse and keyboard [2].…”
Section: Introductionmentioning
confidence: 99%
“…In hand gesture recognition research, vision-based sensors such as depth cameras are widely used [2]. Optical sensors are one example of high-resolution sensors that help to track and recognize finger and wrist movements.…”
Section: Introductionmentioning
confidence: 99%